2012
DOI: 10.1021/bm201771m
|View full text |Cite
|
Sign up to set email alerts
|

CMC-Modified Cellulose Biointerface for Antibody Conjugation

Abstract: In this Article, we present a new strategy for preparing an antihemoglobin biointerface on cellulose. The preparation method is based on functionalization of the cellulose surface by the irreversible adsorption of CMC, followed by covalent linking of antibodies to CMC. This would provide the means for affordable and stable cellulose-based biointerfaces for immunoassays. The preparation and characterization of the biointerface were studied on Langmuir-Schaefer cellulose model surfaces in real time using the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 45 publications
2
70
0
Order By: Relevance
“…Moreover, the negligible non-specific adsorption of human IgG on NFC surface after the superblock treatment allows the use of NFC films in Biointerphases (2012) immunoassays, where positively charged target molecules are monitored. The amount of immobilized antihuman IgG on activated NFC-film was found to be similar to those reported in the literature [5,32]. It should also be mentioned that the adsorbed amount of human IgG on the antihuman IgG interface was over twofold when compared to published results with anti-hIL-1ra conjugation on CMC-PEI hydrogel [5].…”
Section: Biological Activity Of the Immobilized Antihuman Iggsupporting
confidence: 86%
“…Moreover, the negligible non-specific adsorption of human IgG on NFC surface after the superblock treatment allows the use of NFC films in Biointerphases (2012) immunoassays, where positively charged target molecules are monitored. The amount of immobilized antihuman IgG on activated NFC-film was found to be similar to those reported in the literature [5,32]. It should also be mentioned that the adsorbed amount of human IgG on the antihuman IgG interface was over twofold when compared to published results with anti-hIL-1ra conjugation on CMC-PEI hydrogel [5].…”
Section: Biological Activity Of the Immobilized Antihuman Iggsupporting
confidence: 86%
“…Physical adsorptions are usually weak and reversible. However, the adsorption of carboxymethyl cellulose (CMC) onto cellulose surfaces is generally specific and irreversible, (Kargl et al 2012), and thus CMC is widely used as anchoring layers on cellulose surfaces for further modifications Mohan et al 2014;Orelma et al 2011;Orelma et al 2012b;Orelma et al 2012c). Covalent modification can be realized via Bgraft onto^and Bgraft from^approaches.…”
Section: General Methodologymentioning
confidence: 99%
“…Thus, CMC could be utilized as a linker molecule for bioactive molecule immobilization onto cellulose surfaces. Orelma et al, for instance, reported the immobilization of antibodies onto regenerated and nanofibrillar cellulose surfaces using CMC as a linker molecule (Orelma 2012;Orelma et al 2012b;Orelma et al 2012c). Anti-hemoglobin was covalently coupled to CMCmodified cellulose surfaces via EDC/NHS chemistry.…”
Section: Bioactive Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…4C). Previous publications have shown the ability of polysaccharides to adsorb on cellulosic surfaces, providing a convenient way for functionalization (Eronen, Junka, Laine, & Österberg, 2011;Filpponen et al, 2012;Junka et al, 2014;Laine, Lindström, Nordmark, & Risinger, 2000;Liu, Choi, Gatenholm, & Esker, 2011;Pahimanolis et al, 2013;Orelma, Teerinen, Johansson, Holappa, & Laine, 2012;Zemljic, Stenius, Laine, & Stana-Kleinschek, 2008). Accordingly, the synthesized thiopropyl xylan was used to introduce thiol functionalities on the surface of filter paper by a simple dipping-drying method, using a 1 wt% water solution of the xylan derivative.…”
Section: Crosslinking Of Xylan Using Thiol-thiol Couplingmentioning
confidence: 99%